How are Mathematics Teachers Utilizing Technology in Mathematics Learning During the New Normal? - Rosidah, Rosidah; Ikram, Fadhil Zil; Fakhri, M. Miftach; Aprisal, Aprisal; Anaguna, Nursyam (Jurnal MediaTIK, 2023)
The use of technology in Mathematics learning is crucial because it can provide convenience for the learning process. This research is a qualitative study that aims to describe how Mathematics teachers use existing technology or applications in Mathematics learning during the new normal. The participants were three high school Mathematics teachers who utilized technology in their learning. The analysis technique used refers to a three-stage analysis technique which includes data condensation, data display, and conclusion. The results showed that the use of applications available in Mathematics learning varied. Some utilized and maximized various kinds of application features, but some only took advantage of a few main features. There were teachers whose learning activities did not involve too much technology integration and there were also those that involved the use of various applications, even those specifically designed to learn mathematical concepts. The purposes of using applications that can help the teaching and learning process were very diverse. The use almost involves all activities in all teaching and learning processes such as creating, providing, and teaching the teaching materials, assessment, discussion, assignment, and announcements and reminders.